Declining returns of secondary vocational education on subjective class identity across generations and time periods - Penghui Wu; Ming Zhang; Demei Yang (Humanities & Social Sciences Communications)
Abstract This study explores the association of secondary vocational education (SVE) on subjective class identification in China, focusing on comparisons with compulsory and academic high school education, and analyzing regional and historical variations. Using data from the 2013, 2015, 2017, 2018, and 2021 waves of the China General Social Survey (CGSS), this study analyzes 13,736 individuals aged 26 to 58. To address selection bias and better estimate treatment effects, the Generalized Propensity Score Matching (GPSM) method is employed to evaluate the impact of different types of secondary education on subjective class identification. The findings show that individuals with Secondary Vocational Education (SVE) report significantly higher subjective class identification compared to those with only compulsory education, especially in rural areas. While initial comparisons reveal no significant difference between SVE and academic high school graduates, Generalized Propensity Score Matching suggests that academic high school graduates hold higher class identification than SVE graduates. Regionally, education-related class identity gaps are evident in rural but not urban areas. Historically, the positive association between SVE and class identity is significant during 1986–1999, but becomes statistically insignificant during 2000–2010 and 2010-present. SVE significantly enhances subjective class identification compared to compulsory education, particularly in rural areas, with variations across different historical periods. These differences stem from the cyclical development and policy adjustments related to SVE. Therefore, future efforts should focus on strengthening support for SVE, such as expanding opportunities for further education, to maintain the positive association between SVE and subjective class identification.